The Impact of Communication Quality, Teamwork and Trust on Work Productivity of Tanjung Emas Port Employees - Rahmasari, Lisda (LifeSciFi, 2022)
This research aims to examine the influence of communication quality (X1), teamwork (X2), and trust (X3) on work productivity (Y) of Tanjung Emas Port employees in Semarang with a total of 130 respondents. By using the SPSS Regression model tool for data analysis, the results show that the quality of communication, teamwork and trust all have a positive and significant effect on work productivity. Collectively, these variables contribute 50.6% to the diversity of work productivity, and the remaining 49.4% is influenced by other external factors. In hypothesis testing, it was found that communication quality (X1) had a significant positive effect on work productivity (Y), with a calculated t value of 4.376 > t table value of 1.98045, supporting hypothesis 1 (H1). Likewise, teamwork (X2) and trust (X3) both have a positive effect on work productivity (Y), with calculated t values of 2.039 and 4.852 respectively, exceeding the t table value, thus supporting hypotheses 2 (H2) and 3 (H3). These findings underscore the importance of fostering effective communication, teamwork, and trust in the workplace to increase overall productivity.